Characterization of the Biochemical Potential of Moroccan Onions (Allium cepa L.) - Amal Brahimi; Mohamed El Ouardi; Amal Kaouachi; Abdelhakim Boudboud; Lhoussain Hajji; Hassan Hajjaj; Hamid Mazouz (International Journal of Food Science)
Allium cepa L. remains the most cultivated Allium species in Morocco and around the world. With the purpose of making the first biochemical characterization of Moroccan onions, several biochemical components have been measured in eleven onion ecotypes. Onions were collected as seeds from different geographical origins and cultivated in the same environment, to eliminate the influence of the environment on biochemical expression. Moisture, total phenols, flavonoids, antioxidant activity, total and reducing sugars, and sulfur dioxide were the biochemical properties of interest. Except for moisture, the eleven onion ecotypes revealed a highly significant variation in terms of the studied biochemical characters. The total phenol and flavonoid content ranged from 5.94 to 11.22 mg equivalent gallic acid/g dry weight and 0.67 to 1.52 mg equivalent quercetin/g dry weight, respectively. The antioxidant activity of the studied onions showed a strong correlation with the polyphenols (R2=0.7189), especially with the flavonoids (R2=0.8063). The sulfur dioxide content parted from 85.60 to 30.43 ppm when measured using the Monier-Williams distillation method. The current results show that there is no correlation between total sugars and reducing sugars. In conclusion, these findings present a clear biochemical profile of Moroccan onion ecotypes, as well as confirm, for the first time, the presence of a clear variation between the biochemical profiles of Moroccan onion ecotypes, which could be useful for future valorization programs.